2013
DOI: 10.1002/ajh.23559
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune globulins and same‐day thrombotic adverse events as recorded in a large healthcare database during 2008–2011

Abstract: Thrombotic events (TEs) are rare serious complications following administration of hyperimmune globulin (HIG) products. Our retrospective claims-based study assessed occurrence of same-day TEs following administration of HIGs during 2008-2011 and examined potential risk factors using HealthCore's Integrated Research Database (HIRD SM ) and laboratory testing of products' procoagulant Factor XIa activity by U.S. Food and Drug Administration. Multivariable regression was used to estimate same-day TE risk for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 39 publications
6
51
0
Order By: Relevance
“…Variances in rates of TAEs between different IgG products were also noted, with an approximately three‐fold variation overall. The extension of the retrospective study (2008–11) looked at hyperimmune globulin products; the overall rate of TAEs was reported at one‐tenth of that in the initial study (< 0·01%); however, the highest rates were very similar to those observed previously .…”
supporting
confidence: 65%
“…Variances in rates of TAEs between different IgG products were also noted, with an approximately three‐fold variation overall. The extension of the retrospective study (2008–11) looked at hyperimmune globulin products; the overall rate of TAEs was reported at one‐tenth of that in the initial study (< 0·01%); however, the highest rates were very similar to those observed previously .…”
supporting
confidence: 65%
“…13,14,[24][25][26][27][28][29][30][31][32] However, the extent to which these events are attributable to the IVIg itself rather than other risk factors is unclear, as is the risk associated with low doses of IVIg for immunodeficiency. In this retrospective cohort study, we assessed rates of clinically serious arterial and venous TEEs in older patients with CLL or MM who initiated IVIg therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that some off- the-shelf IGIV products were able to generate thrombin and that these same products were contaminated with FXIa [17]. More recent studies found FXIa in batches of IGIV shown to be thrombotic [17, 18] and others, although not based on thrombotic batches, also found an association of FXIa with IGIV products [19, 20, 21, 22]. Another line of evidence is the thrombogenicity of FXI concentrates used to treat FXI deficient patients.…”
Section: Introductionmentioning
confidence: 99%